Relationships between wearer assessment and the instrumental measurement of the handle and prickle of knitted wool fabrics. Issue 11 (July 2015) - McGregor, Bruce A; Naebe, Maryam; Wang, Henry; Tester, David; Rowe, James
The relationships between wearer-assessed comfort and objectively measured comfort and handle parameters were investigated using 19 pure wool single jersey garments made of single ply yarns. Wearer trials were used to determine prickle discomfort, and whether wearers "liked" the garments. Fabrics then were objectively evaluated using the Wool HandleMeter, which measures seven primary handle attributes; and the Wool ComfortMeter (WCM), to predict a wearer's perception of fabric-evoked prickle. Wearer responses and the relationships within and between objective measurements and the effect of fibre, yarn and fabrics attributes were analysed by general linear modelling. Mean fibre diameter, fibre diameter coefficient of variation, yarn count, fabric thickness, fabric density, fabric mass per unit area and decatising affected one or more handle parameters. The best model for predicting wearer prickle discomfort accounted for 90.9% of the variance and included only terms for the WCM and WCM 2 . The WCM was a good predictor whereas mean fibre diameter was a poor predictor of whether wearers "liked" garments. Wearer assessment of prickle and whether or not wearers "liked" fabrics were independent of fabric handle assessment. The results indicate that the handle and comfort properties of lightweight, wool jersey fabrics can be quantified accurately using the Wool HandleMeter and the Wool ComfortMeter. For fabric handle, fibre and yarn characteristics were less important than changes in the properties of the fabric.